Penerapan Augmented Reality Pada Brosur Smartphone Menggunakan Algoritma FAST Corner Detection - Savanah Sekar Arum; Iskandar Fitri; Rini Nuraini (LPPM UBHINUS MALANG, 2021)
Technological advances in the globalization era, widely utilized in various fields, one of which is in the field of business. For example, in promotional media, the presence of augmented reality technology which is a technology that brings 3D virtual objects created using computers, into the real world of 3D. The way augmented reality works itself is by tracking markers through a camera that acts as an eye that can recognize objects and then project in real time. Therefore, the technology will be applied to this research, which discusses the application of augmented reality in smartphone brochures with FAST Corner Detection (FCD) algorithm. The purpose of using augmented reality technology in this brochure, to make the reader can see 3D objects in the brochure using the smartphone augmented reality application that can be installed on the reader's smartphone. And the function of using FCD algorithm itself is to recognize markers by tracking the central points (angles) in the marker image. The test result of this study is that the application can be used well to scan markers at a sufficient intensity of light to a lot of light and with a distance of â‰¤50 cm - <80 cm from the AR camera to the marker.